Sikap Pelajar Asing dalam Memahami Pesan Komunikasi Antarbudaya - Nabilah, Septa Widya Etika Nur Imaya; Suyitno, Imam; Zahro, Azizatuz (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research is motivated by phenomena that occur in the context of learning Indonesian as a foreign language related to intercultural communication activities between foreign students and Indonesians in general (BIPA teachers, language partners, and local people), for example related to intercultural communication barriers and attitudes, anda attitudes that shown by foreign students in intercultural communication. This research is aimed to describe the (1) negative attitudes and (b) positive attitudes of foreign students in understanding the message in intercultural communication. This research is descriptive-qualitative research based on phenomena that appear in BIPA learning. The data in this research is taken from the questionnaires and in-depth interview with foreign students. The results are three negative attitudes, there are (a) denial, (b) defense or reversal, and (c) minimization and three positives attitudes, there are (a) acceptance, (b) adaptation, and (c) integration shown by foreign students in understanding messages in intercultural communication. This research can contribute thoughts and insights and can be used as a reference in further researching intercultural communication. In addition, it can also be used by foreign students and Indonesians in general, such as BIPA teachers, language partners, and local people as references in intercultural communication.